Case report: Extrapontine myelinolysis combined with flupentixol- and melitracen-induced dysphagia - Zhao, Zhihong; Han, Lu; Zhu, Zilong (Frontiers in Pharmacology, 2023)
Extrapontine myelinolysis (EPM) is a rare symmetrical demyelinating disease of central nerve system, which is often concomitant with central pontine myelinolysis (CPM) or can appear alone. Flupentixol and melitracenisan antianxiety-antidepressant drug which may cause hyponatremia. We report a 46-year-old woman who had taken flupentixol and melitracen 0.5 mg/10mg once daily for depression for six months. The dosage increased to 0.5 mg/10 mg twice daily later. At the same time, she had also complained of intermittent dizziness and fatigue. Laboratory test revealed hyponatremia(121 mmol/L). Dizziness was improved after sodium supplementation raising the serum sodium to 133 mmol/L. Twenty days later, She had difficulty opening the mouth and swallowing, needing a gastric tube for severe dysphagia. Head magnetic resonance imaging (MRI) showed a symmetric abnormal signal of caudate nucleus and lenticular nuclei. The symptoms were not relieved after active treatment, such as rehydration.However, her symptoms improved significantly after discontinuation of the flupentixol and melitracen and switching to promethazine. Follow-up head MRI 4 months later revealed no abnormal signals. The patient who developed EPM had dysphagia despite appropriate correction of hyponatremia. Flupentixol and melitracen can cause hyponatremia and dysphagia. This case highlights an unexpected association between EPM and flupentixol and melitracen-induced dysphagia.